George Kennan and Kazakhstan. From the book «Siberia and the Exile System» (Herald of Journalism, 2018)
The material contained in the book by American writer and journalist George Kennan’s «Siberia andthe Exile System», has greatly expanded information about the life of political exiles. Kennan’s book,caused deep dissatisfaction with the ruling circles of Russia and got a worldwide repercussions. The mainvalue for modern historical science and the history of journalism represents information about the life ofKazakhs collected by a foreign author. The analysis of the material showed that everything connectedwith the life, present and future of the Kazakh people, illuminated, considered, evaluated from the pointof view of socio-economic development of Russia.